PENGARUH PROBLEM POSING MENGGUNAKAN ALAT PERAGA TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA - pradanika, siti nur; ulum, badriyatul (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2018)
This study aims to determine the effect of learning model problem posing using props to motivation and mathematics learning outcomes in the geometry subject matter on students VIII grade SMPN 1 Sendang. The approach used is quantitative in the form of experimental research. The results of this study include: (1) results of mathematics learning with conventional learning outcomes in the geometry subject matter on grade VIII students an average of 71.6; (2) the result of learning mathematics with problem posing learningin the geometry subject matter on grade VIII students an average of 77,8; (3) there is influence of problem posing learning model to the result of students learning mathematics which magnitude of 10,3%.Â Keywords: problem possing, learning mathematics outcomes